PENINGKATAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN METODE JIGSAW PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS V SD NEGERI 29 RANTAU BATU PASAR - Putri, Cintia Pratama; Sari, Nauli Tama (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The achievement of learning objectives is inseparable from the primary role of the teacher. A teacher is not only required to impart knowledge, but also to create a pleasant learning environment so that the learning process can proceed actively. Purpose of this study is to improve the learning outcomes of fifth-grade Indonesian students by using the jigsaw method in Indonesian language learning at SDN 29 Rantau Batu Pasar in the 2024/2025 academic year. As a classroom action research (CAR), the research instruments used were teacher activity sheets, affective assessment sheets, and learning outcome test sheets. The procedure consists of 4 stages: planning, implementation, observation, and reflection. The results of this study indicate that students' comprehension ability (C2) can be improved by using the Jigsaw method, where in Cycle I there was an increase from 67% to 69%, and in Cycle II it increased to 78,1%. While the ability of cooperation (A2) increased from 56% to 72%, and in Cycle II. Thus, it is clear that the learning outcomes of fifth-grade Indonesian at SDN 29 Rantau Batu Pasar can be improved by applying the Jigsaw Method.